Exercise as a diagnostic and therapeutic tool for the prevention of cardiovascular dysfunction in breast cancer patients. (29th August 2020) - Howden, Erin J; Bigaran, Ashley; Beaudry, Rhys; Fraser, Steve; Selig, Steve; Foulkes, Steve; Antill, Yoland; Nightingale, Sophie; Loi, Sherene; Haykowsky, Mark J; La Gerche, André
Abstract: Background: Anthracycline chemotherapy may be associated with decreased cardiac function and functional capacity measured as the peak oxygen uptake during exercise (V · O 2 peak). We sought to determine (a) whether a structured exercise training program would attenuate reductions in V · O 2 peak and (b) whether exercise cardiac imaging is a more sensitive marker of cardiac injury than the current standard of care resting left ventricular ejection fraction (LVEF). Methods: Twenty-eight patients with early stage breast cancer undergoing anthracycline chemotherapy were able to choose between exercise training (mean ± SD age 47 ± 9 years, n = 14) or usual care (mean ± SD age 53 ± 9 years, n = 14). Measurements performed before and after anthracycline chemotherapy included cardiopulmonary exercise testing to determine V · O 2 peak and functional disability (V · O 2 peak < 18 ml/min/kg), resting echocardiography (LVEF and global longitudinal strain), cardiac biomarkers (troponin and B-type natriuretic peptide) and exercise cardiac magnetic resonance imaging to determine stroke volume and peak cardiac output. The exercise training group completed 2 × 60 minute supervised exercise sessions per week. Results: Decreases in V · O 2 peak during chemotherapy were attenuated with exercise training (15 vs. 4% reduction, P = 0.010) and fewer participants in the exercise training group met the functional disability criteria after anthracycline chemotherapy compared with those in the usual care group (7 vs. 50%, P = 0.01). Compared with the baseline, the peak exercise heart rate was higher and the stroke volume was lower after chemotherapy ( P = 0.003 and P = 0.06, respectively). There was a reduction in resting LVEF (from 63 ± 5 to 60 ± 5%, P = 0.002) and an increase in troponin (from 2.9 ± 1.3 to 28.5 ± 22.4 ng/mL, P < 0.0001), but no difference was observed between the usual care and exercise training group. The baseline peak cardiac output was the strongest predictor of functional capacity after anthracycline chemotherapy in a model containing age and resting cardiac function (LVEF and global longitudinal strain). Conclusions: The peak exercise cardiac output can identify patients at risk of chemotherapy-induced functional disability, whereas current clinical standards are unhelpful. Functional disability can be prevented with exercise training.